Clinical outcomes of LeFort colpocleisis: a single-center experience from Turkey - Isenlik, Bekir Sitki; Aygun , Bilgesu Cetinel; Tekin, Erinc; Han, Orkun; Inal, Hasan Ali (Vojnosanitetski pregled, 2024)
Background/Aim. LeFort colpocleisis (LFC) is a procedure for treating pelvic organ prolapse (POP) in women. The aim of the study was to assess the sociodemographic characteristics, anatomical outcomes, satisfaction, and clinical outcomes of patients who underwent LFC for POP. Methods. The study retrospectively and consecutively included 103 patients who underwent LFC for stage III and stage IV POP between January 2010 and December 2022. The participants’ sociodemographic characteristics and clinical outcomes were documented. The Turkish version of the Pelvic Floor Distress Inventory (PFDI-20) questionnaire was used to determine quality of life. Results. The patients’ mean age was 73.1 ± 26.7 years, mean body mass index 27.4 ± 3.8 kg/m2, parity 4.8 ± 1.5, smoking rate 12.6%, POP quantification (POP-Q) stage III 30.1%, and POP-Q stage IV 69.9%. Their satisfaction rate results were 93.3%. Significant differences were observed in the preoperative period compared to the postoperative period in constipation (40.7% vs. 26.2%; p = 0.038), difficult defecation (22.3% vs. 8.7; p = 0.012), fecal incontinence (18.4% vs. 7.7%; p = 0.039), stress urinary incontinence (25.2% vs. 4.8%; p < 0.001), urge incontinence (49.5% vs. 27.1%, p = 0.001), voiding dysfunction (37.8% vs. 23.3%; p = 0.002), and urinary retention (42.7% vs. 12.6%; p < 0.001). Postoperative PFDI-20 scores were also significantly lower compared to the preoperative period (57.19 ± 16.57 vs. 21.62 ± 6.96; p < 0.001). Conclusion. This study showed that LFC has been established as a surgical procedure with high anatomical success, high patient satisfaction rates, and minimal complications, especially in advanced POP with age-related comorbidities.
Keywords: gynecologic surgical procedures; pelvic organ prolapse; quality of life; surveys and questionnaires; women